Health promoting schools and COVID-19: preparing for the future. Issue 6 (August 2022) - Sormunen, Marjorita; Lattke, Lynda; Leksy, Karina; Dadaczynski, Kevin; Sakellari, Evanthia; Velasco, Veronica; Borzucka-sitkiewicz, Katarzyna; Miranda-velasco, María J.; Rabaglietti, Emanuela; Rosário, Rafaela
We face an unprecedented period of history during which COVID-19 is clustered with other global conditions, such as obesity, undernutrition, an infodemic, and climate change. This syndemic (synergy of epidemics) calls for the development of children's and youth's health literacy and socioemotional skills, support for behavioural hygiene (e.g. washing hands, wearing masks), and adults' responsibility and caring. Moreover, it calls for creating conditions for healthy living and learning for all and paying extra attention to inequalities that have increased during the pandemic. Today, more than ever, there is an essential demand for schools to create environments that maintain and promote health for all. Within this commentary, we argue that whole-school approaches, such as the health promoting school, are essential to fight against the pandemic and to prepare schools for future challenges.